Efektivitas Pemberian Buah Bit (Beta Vulgaris Subsp.) Terhadap Anemia Pada Ibu Prakonsepsi - Sampara, Nurqalbi; Muzakkir, Muzakkir (Madu : Jurnal Kesehatan, 2023)
Preconception is a critical period for every woman of childbearing age (WUS), which determines the quality of the baby born. Researcher Objectives This study aims to determine the effectiveness of giving beet fruit (Beta et al.) on Anemia in Preconception Mothers in the Tanakaraeng Village Working Area. This research design uses a Quasi-Experimental design with a Pretest-Posttest With Control design with a nonequivalent control group design method, namely before being given both the experimental and control groups. Based on the unpaired T-test statistical test (independent sample T-test). It was found that the significant value of 0.003 was smaller than 0.05. There is a significant difference in the results of the study because the significant value is smaller than 0.05, and it can be seen that the average value or mean in the post-test giving beetroot fruit is 11.6, and in the post-test giving Fe tablets is 10.6. This value means that the average giving of beet fruit with Fe tablets is higher than that of Fe tablets. Pregnant women are expected to consume foods with high iron content.